STRENGTHENING THE CROSS-BORDER COLLABORATION ECOSYSTEM: NETWORKING AND COMPETITIVENESS IN SMES - Syamsul Hadi; Rima Sotlikova; Bernadetta Diansepti Maharani; Auliya Rosiana; Dika Prawita (SMARTINDO, 2026)
The fashion Micro, Small, and Medium Enterprises (MSME) sector faces continuous challenges in expanding international networks, managing supply chains, and overcoming uneven digital adoption in the global market. This community service activity aimed to strengthen the cross-border collaboration ecosystem and enhance the competitiveness of the Muslim fashion SME